Karakteristik Fisikokimia dan Organoleptik Mi Basah Berbasis Tepung Pisang Goroho (Musa acuminate) Dengan Penambahan Sari Daun Gedi (Abelmoschus manihot) - ukus, jacklin; Taroreh, Mercy I.R.; Kandou, Jenny (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2025)
The purpose of this study was to analyze the effect of the addition of gedi leaf extract on the physical and chemical characteristics of wet noodles based on goroho banana flour, and to evaluate the level of panelists' preference for the color, taste, and texture of wet noodles based on goroho banana flour with the addition of gedi leaf juice. The method used in this study was a Completely Randomized Design (CRD) with a formulation of 80% wheat flour and 20% goroho banana flour, with the addition of gedi leaf juice formulation A (20% addition of green gedi leaf juice). B (25% addition of green gedi leaf juice), C (30% addition of green gedi leaf juice), D (35% addition of green gedi leaf juice) with three replications. The results showed that the physical characteristics of wet noodles based on goroho banana flour with the addition of gedi leaves at cooking time ranged from 1.58-5.60 minutes, cooking loss ranged from 24.56-27.07%, and water absorption capacity of 44.60-72.00%. Chemical characteristics of crude fiber between 3.04- 4.55%, and antioxidant activity 37.5-50.36. The results of the panelists' preference level test for wet noodles based on goroho banana flour with the addition of ged leaf extract showed that the taste ranged from 4.16-4.36 (Somewhat like), texture between 4.76-4.96 (Somewhat like), color ranged from 4.36-5.24 (Somewhat like).